Challenges in the management of intracranial hypertension in pediatric patients with HIV: a case report - Cifuentes, Amelia; Arellano, Karolina; Lapo, Nathaly; Vásconez-Gonázlez, Jorge; Izquierdo-Condoy, Juan S.; Ortiz-Prado, Esteban (Frontiers in Medicine, 2025)
IntroductionThe HIV epidemic is often primarily associated with key populations at higher risk of transmission, which has led to an underestimation of its impact on the pediatric population. In children, the disease may go unnoticed due to the delayed onset of symptoms, and diagnosis is often made at advanced stages, once opportunistic infections have already appeared such as cryptococcal meningitis, which carries high morbidity and mortality rates.Case reportA 13-year-old adolescent, newly diagnosed with WHO clinical stage IV HIV infection (unknown transmission route), was admitted with a central nervous system opportunistic infection caused by Cryptococcus neoformans. The patient presented with fever and seizures; the diagnosis was confirmed by positive India ink staining. Management, led by the Pediatric Infectious Diseases and Neurology services, focused on controlling intracranial hypertension (ICH) through 12 successive lumbar punctures for cerebrospinal fluid (CSF) drainage. Despite this aggressive multidisciplinary approach, the patient developed bilateral blindness secondary to chronic papilledema. This case highlights the challenges of advanced HIV in adolescence and the crucial need for effective ICH management in cryptococcal meningitis.DiscussionCryptococcosis is one of the most severe opportunistic infections in immunocompromised patients, and its management in children and adolescents lacks standardized guidelines, which further complicates treatment. In this case, the absence of an external CSF drainage system and the need for multiple lumbar punctures highlight the therapeutic limitations in managing intracranial hypertension in resource-limited settings. This patient’s history shows that with appropriate care and a committed interdisciplinary team, it is possible to improve the quality of life for pediatric HIV patients, even in complex clinical scenarios.ConclusionEarly detection of HIV in children and adolescents must be strengthened, along with optimizing access to timely treatment to reduce the impact of opportunistic infections. Ongoing training should be promoted for healthcare professionals managing immunodeficient patients, as adherence to updated protocols and an interdisciplinary approach can make a significant difference in the prognosis and quality of life of these patients.